Rights of Minors in the Sphere of Culture, Recreation and Leisure Activities - Prokhorova, Larisa Viktorovna; Rabets, Anna Maximovna; Tchinaryan, Elena Olegovna; Markosyan, Anait Vyacheslavovna (International Review of Management and Marketing, 2016)
The works is dedicated to highly challenging though poorly investigated problems of legislative recognition and practical implementation of rights of minors in the sphere of culture, recreation and leisure activities. Detailed analysis of international legislative acts and laws of the Russian Federation regulating public relations in this sphere leads the investigators to a conclusion on obvious insufficiency of statutory regulation of these relations in respect to minors in spite of a high degree of significance of corresponding standards for provision of full-scale physical, psychic, moral and intellectual development of personality of a young person. Work may be useful for scientists, teachers, candidates and students of law schools as well as for practitioners whose activity is connected with protection of rights and interests of minors and (or) with their physical, moral and artistic education. Keywords: children, minors, recreation, culture, leisure activities, physical culture, physical education, sport, aesthetic education, artistic education, JEL Classifications: Z13, Z18, K39